Acute hyperlipidemia but not hyperhomocysteinemia impairs reflex regulation of the cardiovascular system. (May 2015) - Reimann, Manja; Rüdiger, Heinz; Weiss, Norbert; Ziemssen, Tjalf
Abstract: Background: Elevated circulating lipids and homocysteine may affect autonomic cardiovascular function by decreasing baroreflex sensitivity (BRS) and cardiovagal outflow and by increasing sympathetic drive. Methods: To test this hypothesis 25 clinically healthy men (mean age 24 ± 2 years) received 500 ml whipping cream (30% fat) and 0.1 g/kgl -methionine, respectively, at intervals of one week apart to induce hyperlipidemia and hyperhomocysteinemia, respectively. Cardiovascular parameters and endothelial function were assessed before and 2 h after the fat load and before and 4 h after the methionine load, respectively. Cardiovascular responses to sublingual application of a nitrovasodilator and a beta-agonist were also determined. Results: Hyperlipidemia elicited a significant decline in BRS and an increase in heart rate and sympathetic drive. Reductions in BRS were associated with changes in total cholesterol but not with triglycerides or endothelial function. Autonomic and hemodynamic variables remained unaltered during transient hyperhomocysteinemia although there was a trend to lower BRS. Autonomic and hemodynamic responses to pharmacological vasodilation and beta-adrenoceptor stimulation were preserved under both conditions. Conclusions: These data provide experimental support for the concept that acute hyperlipidemia but not hyperhomocysteinemia impairs reflex regulation of the circulatory system.